2013
DOI: 10.2967/jnumed.112.118877
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the In Vivo Selectivity of a New κ-Opioid Receptor Antagonist PET Tracer 11C-LY2795050 in the Rhesus Monkey

Abstract: [11C]LY2795050 is a novel kappa-selective antagonist PET tracer. The in vitro binding affinities (Ki) of LY2795050 at the kappa opioid (KOR) and mu opioid (MOR) receptors are 0.72 and 25.8 nM, respectively. Thus, the in vitro KOR/MOR binding selectivity is about 36:1. Our goal in this study was to determine the in vivo selectivity of this new KOR antagonist tracer in the monkey. Methods To estimate ED50 value of LY2795050 at the MOR and KOR sites, two series of blocking experiments were performed in three rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
1
25
1
Order By: Relevance
“…Using the in vitro (0.72 nmol/L (9)) and in vivo (0.028 nmol/L (12)) K D values, the occupancy by carrier mass in all scans was calculated as <0.2% and <3%, respectively. In our previous study in rhesus monkeys (11), the LY2795050 ED 50 at KOR was estimated as 15.6 μg/kg. Using this ED 50 value, the occupancy by LY2795050 was < 1.5% in all scans.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Using the in vitro (0.72 nmol/L (9)) and in vivo (0.028 nmol/L (12)) K D values, the occupancy by carrier mass in all scans was calculated as <0.2% and <3%, respectively. In our previous study in rhesus monkeys (11), the LY2795050 ED 50 at KOR was estimated as 15.6 μg/kg. Using this ED 50 value, the occupancy by LY2795050 was < 1.5% in all scans.…”
Section: Discussionmentioning
confidence: 97%
“…This new tracer has been examined in both nonhuman primates (10, 11) and human subjects (12). Our previous analysis of human imaging data found that 150 mg oral dose of naltrexone blocked ~90% KOR across all brain regions, which suggests the absence of a suitable reference region for 11 C-LY2795050 in the human brain, and that the lowest inter-subject variability in three versions of binding potential ( BP ND , BP P , BP F ) was observed when the non-displaceable distribution volume ( V ND ) was estimated as a fixed fraction of cerebellum V T ( V T , CER = 1.17 V ND ).…”
Section: Introductionmentioning
confidence: 99%
“…Most human studies reviewed here pertain to the μ system, although animal studies have established that different types of opioid receptors have distinct influences on mood‐related processes (Lutz and Kieffer, ). Accordingly, future human studies should exploit advances in PET radiochemistry and address the contribution of δ (Madar et al, ) and κ (Kim et al, ; Vijay et al, ) receptors to emotions. Finally, inducing emotions in human subjects in the laboratory is far from straightforward.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…LY2795050 is a part of a new class of kappa opioid receptor (KOR) antagonist drugs and was reported to have good selectivity for KOR over the mu opioid receptor (MOR) (36:1 KOR:MOR) in a cellular assay (Mitch et al, 2011). To determine the in vivo selectivity for this drug, a PET occupancy study was conducted in rhesus monkeys, utilizing radiolabeled [ 11 C]LY2795050 (KOR radiotracer) and [ 11 C]carfentanil (MOR radiotracer) to assess opioid subtype selectivity (KOR:MOR) (Kim et al, 2013). Animals were treated with the KOR antagonist drug LY2795050 at six doses (1.6 – 400 µg/kg, i.v.)…”
Section: Drug Occupancy and Radiotracer Competitionmentioning
confidence: 99%